Efeito da temperatura e do tempo de armazenamento de amostras de leite cru nos resultados das análises eletrônicas - Almeida , Thamara Venâncio de (2015)
For assessing compliance with the quality requirements established by the Normative Instruction No. 62, a milk sample each property or community tank should be analyzed on a monthly basis by one of the laboratories accredited by the Brazilian Laboratories Network for Milk Quality Control . There are still doubts about what would be the maximum temperature and the time of milk sample storage without jeopardizing the results of the electronic analysis. The objective of this study was to evaluate the effects of temperature and storage time of cooled samples of raw milk on the results of milk quality electronic analysis. Refrigerated raw milk samples were collected from expansion tanks for individual use of farms located in the middle region of the state of Goiás, and stored at four different temperatures (3 °C, 11 °C, 17 °C and 25 °C) for 16 days. Total bacterial count (TBC), somatic cell count (SCC) and chemical composition were performed daily. The results were submitted to analysis of variance in split plot design in randomized blocks, and the means were compared by Duncan test. We concluded that, when azidiol is added as preservative to samples for TBC, they can be analyzed up to 16 days after collection when stored at temperatures of 3 °C and 11 °C, and up to 10 days when stored at 17 °C. Moreover, when bronopol is added as preservative, samples for SCC and chemical composition analysis can be stored for up to 16 days after collection when stored at temperatures of 3 °C and 11 °C, and for up to seven days when stored at 17 °C.